Internet: managers' vision - Bose, Surojit; Kishore, S. (1996)
`Internet' is the latest buzzword in India. With the reduction in the prices of computers and the advancement in the field of telecommunication and technology, the Internet phenomenon has gripped the Indian imagination. The `on-line' experience has arrived with the clarion calls of globalization and liberalisation of the Indian economy. This paper explores how this new-world technology called Internet can help Indian managers to think global and achieve new vision - Reproduced
Keywords: Internet